671. Math. Lempertz'sche Kunstversteigerung : Zeitgenössische Kunst = Contemporary Art. - Hanstein, Henrik Rolf (Köln : Kunsthaus Lempertz Köln, 1991)
Alechinsky, Pierre ; Alt, Otmar ; Altenbourg, Gerhard ; Alviani, Getulio ; Antes, Horst ; Appel, Karel ; Arman ; Arp, Hans (Jean) ; Baj, Enrico ; Barry, Robert ; Baselitz, Georg ; Baumgarten, Bodo ; Beck, Gerlinde ; Berke, Hubert ; Beuys, Joseph ; Biel, Michael von ; Bill, Max ; Blais, Jean-Charles ; Blume, Bernhard Johannes ; Bogart, Bram ; Bonato, Victor ; Brauer, Arik ; Brecht, George ; Broodthaers, Marcel ; Brüning, Peter ; Brus, Johannes ; Bühl, Hede ; Buren, Daniel ; Buthe, Michael ; Calder, Alexander ; Calderara, Antonio ; Castelli, Luciano ; Castillo, Jorge ; Cavael, Rolf ; Chadwick, Lynn ; Chevalier, Peter ; Chillida, Eduardo ; Christo ; Clave, Antoni ; Corneille ; Cruz-Diez, Carlos ; Dahmen, Karl Fred ; Dahn, Walter ; Darboven, Hanne ; Davie, Alan ; Dibbets, Jan ; Dokoupil, Jiri Georg ; Dorazio, Piero ; Droese, Felix ; Dubuffet, Jean ; Erb, Leo ; Erben, Ulrich ; Errò ; Fabro, Luciano ; Fetting, Rainer ; Fischer, Lothar ; Riverhead (New York) ; Fontana, Lucio ; Förg, Gunther ; Francis, Sam ; Friedlaender, Johnny ; Fröhlich, Fritz ; Fruhtrunk, Günter ; Fuchs, Ernst ; Fussmann, Klaus ; Galli ; Gaul, Winfred ; Gecelli, Johannes ; Geiger, Rupprecht ; Gerdes, Ludger ; Gille, Sighard ; Girke, Raimund ; Gläsker, Horst ; Goepfert, Hermann ; Gonschior, Kuno ; Götz, K.O. (Karl Otto) ; Graeff, Werner ; Graubner, Gotthard ; Grochowiak, Thomas ; Grützke, Johannes ; Guarneri, Riccardo ; Hahn, Friedemann ; Hajek, Otto Herbert ; Hallmann, Blalla W. ; Hamilton, Richard ; Haring, Keith ; Hartung, Hans ; Heerich, Erwin ; Heisig, Bernhard ; Helmus, Roland ; Hennig, Albert ; Herkenrath, Peter ; Herold, Georg ; Hiltmann, Jochen ; Höckelmann, Antonius ; Hockney, David ; Hödicke, Karl Horst ; Hoehme, Gerhard ; Hofschen, Edgar ; Hrdlicka, Alfred ; Hundertwasser ; etc.
biografie
Duits
Engels
boek